Multi‐Mode Triboelectric Nanogenerator for Football Impact Monitoring and Mechanical Energy Harvesting - Xi Chen; Xiaolong Yu (ChemistryOpen)
Abstract The integration of digital products and sensors significantly enhances motion monitoring accuracy, addressing the limitations of hawk‐eye technology. Triboelectric nanogenerators (TENGs) provide innovative, low‐cost solutions for developing intelligent digital motion monitoring systems. In this study, we designed a multi‐mode triboelectric nanogenerator (M‐TENG) that incorporates multiple working modes, enabling switching between internal electrodes to adjust the output mode. This dual working mode enhances the adaptability of the device for football monitoring applications. The versatile design allows the M‐TENG to perform both energy harvesting and trigger‐based sensing and monitoring, contributing to the advancement of digital intelligence movement technologies. After optimization, the M‐TENG achieved a transferred charge (Qsc) of 88.38 nC, short‐circuit current (Isc) of 8.58 μA, and open‐circuit voltage (Voc) of 85.91 V, showcasing excellent electrical performance. The device charged a 1 μF capacitor to 5 V in 36 seconds, delivering a peak power of 178 μW, and maintained stable output with only a 14 % decrease over 60 days. Additionally, the M‐TENG effectively detects and harvests energy from football impacts, generating consistent voltage signals from each interaction, making it a promising candidate for real‐time sports equipment monitoring without the need for an external power source.